On the use of the MOORA method in the selection of investment projects - Filipe, J.; Caleiro, A. (MCDM methods for business and management, 2020)
As is well known, when faced with the problem of decision-making, involving several (eventually conflicting) objectives evaluated according to several criteria, multi-criteria analysis is one of the most appropriate methodologies to support the decision. The flexibility of multi-criteria decision analysis/making is one of its most recognized characteristics, which comes from the various methods that can be considered. Among them is the so-called MOORA (as the initials of Multi-Objective Optimization by Ratio Analysis) method.